An insight into the reproductive biology of the bearded goby Sufflogobius bibarbatus. Issue 2 (25th January 2013) - Utne‐Palm, A. C.; Locatello, L.; Mayer, I.; Gibbons, M. J.; Rasotto, M. B.
<x xml:space="preserve">Abstract</x> Preliminary results obtained from histological analyses of the male reproductive organs, supplemented with field and behavioural data, indicate that Sufflogobius bibarbatus, a small, slow growing gobiid exhibiting low fecundity, which plays an important role in the food web off Namibia, where large areas of the shelf are hypoxic, spawns demersally. Large males defend benthic nests, possibly at the edge of the hypoxic shelf. Male reproductive strategy appears to be flexible, and tentative evidence to suggest that polygyny and sneaking may also occur is presented.